Memetising the pandemic: memes, covid-19 mundanity and political cultures. Issue 16 (10th December 2021) - Murru, Maria Francesca; Vicari, Stefania
ABSTRACT: It was late February 2020 when part of Northern Italy entered the first Covid-19 lockdown of the West. While stories of people fleeing quarantined areas soon made national headlines, the international news was suddenly reporting of coronavirus patients connected to Italy all around the world. Against this background, Italian social media started thriving with Covid-19 humour. On 9 March the lockdown turned nationwide and became one of the strictest in Europe. This article addresses everyday memes of quarantined Italy as an instance of mundane memetics at a time of crisis. It investigates the leading discourses emerging from these memes to provide insight into the political culture that surfaces at the intersection between the ordinary of everyday social media uses and the extraordinary of crisis events. We combined digital methods and netnographic techniques to generate and analyse a dataset of over 9, 000 Covid-19 memetic instances produced on Twitter by Italian publics during the first national lockdown. Our findings show that in early everyday pandemic memes the political stake did not manifest itself in the explicitness of values, attitudes, and knowledge tightly packaged in a purposeful and self-aware political culture. It rather surfaced in the form of a mundane political culture – one that was primarily performative, irrespective of any future political action, and marked by populist values.